MODEL KOMUNIKASI KEPEMIMPINAN BIDANG HUBUNGAN ANTAR LEMBAGA: Studi kasus pada Badan Penghubung Pemerintah Provinsi Riau di Jakarta - Najib (Indra Institute Research & Publication, 2024)
This research aims to find the right communication model and apply it to the leadership of the Inter-Agency Relations sub-sector in the Riau Provincial Government Liaison Agency in Jakarta. The theory used is leadership theory in general and leadership communication in organizations in particular. Researchers used qualitative methods with a case study approach and data collection techniques through interviews with leaders as decision or policy makers as well as staff in the sub-sector of Inter-Institutional Relations in the Riau Provincial Government Liaison Agency as well as using observation methods on existing reports. The result of this research is the discovery of a communication model that is relevant to be applied to leadership in the sub-field of Inter-Institutional Relations, namely a democratic communication model with a participatory approach. The conclusion of this research is that leadership in an organization should involve staff before making decisions or policies. The success of leadership is determinedby internal success first.